Modern Architecture in the Promotion of National Tourism, the Cap Ducal, an Emblematic Work in Viña del Mar - Cortés, Macarena (Docomomo Journal, 2015)
This article proposes analyzing the Cap Ducal restaurant, a work by architect Roberto Dávila Carson in 1936, as an emblematic construction in Chile’s favorite summer resort city, Viña del Mar. The proposal is to place the relevance and value of this pioneer work of modernity in a wide context of promotion, in which it represents the changes in social and cultural practices related to the resort. From the realm of architecture where, this work establishes the beginning of a new formal language, as well as a part of the new urban configuration of the city as one of the then new tourist infrastructure works.